VMAT 2D ISODOSE CURVE ANALYSIS AS A RESULT OF MONTE CARLO SIMULATION IN LUNG CANCER WITH 6MV PHOTON BEAM - NURAMDIANI (NIM: 20214031), DIAN
Radiotherapy is one of the major modality in cancer treatment. VMAT (Volumetric Modulated Arc Therapy) is a radiotherapy technique which provides a continuous full dose radiation as the gantry rotates (dynamic beam delivery). This technique is achieved by arranging three variables which change simultaneously as the treatments take place. They are: gantry rotation speed, beam cross-sectional shape arranged by MLC leaf position, and fraction of the given dose. Calculation of radiation dose before administration of treatment needs to be done to achieve the goal of radiotherapy. The aim of this study is to conduct Monte carlo VMAT simulation using EGSnrc code system / DOSXYZnrc to determine dose distribution of radion in lung cancer with parameters data derived from the rtplan. The phantom used comes from CT scans thorax data which is read by ctcreate. Simulation is repeated by dividing the number of control points of VMAT into 38 simulations with each repetition of simulation consists of three pieces of control point. Repetition of simulation is done to overcome the limitations of computer specifications in simulating. History number of particles used in each repetition is 2 x 107 particles, therefore the total of particles history used is 7,6 x 108. Simulation output file is .3ddose containing data dose calculation, further processed and analyzed by simple descriptive statistical methods to shape the isodose curve. As a comparison, simulation VMAT with all of control point at a time also conducted by using the number of history 6 x 107 particles. The results suggest that the dose distributions formed from the sum of data from all simulations with 3 control points tend to have a similar pattern to the dose distribution form of simulations involving all control points, but the ratio of the amount of particles history used to form the curve isodosis between both of simulations can not be known with certainty yet. The standard deviation of the dose simulation still has a relatively large value, with the doses standard deviation of voxel were observed at around the isocentre is 31,2%. So the simulation by dividing the number of control points VMAT remains to be studied further in order to be one solution to overcome the limited computer specification problem in performing Monte Carlo simulations.